1984
DOI: 10.1115/1.3243097
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Structures in the Similarity Region of Two-Dimensional Turbulent Jets

Abstract: The strongest indication of an ordered structure in the similarity region of plane jet flows is the well documented (but controversial) apparent “flapping” behavior. Previously, the negative correlation between probes placed on opposite sides of the jet centerline has been attributed to the periodic displacement of the mean velocity profile centerline about its average position, i.e., a flapping motion. The present investigation is directed at evaluating the premise of an essentially two-dimensional von Karman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…Wygnanski & Petersen (1987) have noted that the linear modes of instability in the wake are the same as in the plane jet (mean velocity profiles in both flows have two inflection points). The topological information obtained by and the measurements of Oler & Goldschmidt (1981, 1982 and Thomas & Goldschmidt (1986) support the existence of an alternating pattern in the far field of the plane jet, as in the far wake.…”
Section: Introductionmentioning
confidence: 61%
“…Wygnanski & Petersen (1987) have noted that the linear modes of instability in the wake are the same as in the plane jet (mean velocity profiles in both flows have two inflection points). The topological information obtained by and the measurements of Oler & Goldschmidt (1981, 1982 and Thomas & Goldschmidt (1986) support the existence of an alternating pattern in the far field of the plane jet, as in the far wake.…”
Section: Introductionmentioning
confidence: 61%
“…Many experimental studies and results are available on jets. [1][2][3][4][5][6][7][8][9][10][11][12][13] Characteristics in the near field of the jet nozzle as well as in the self-preservation region have been investigated. Large statistical structures are seen, especially in the near field, that include a Von Karman vortex street and rollerlike structures.…”
Section: Introductionmentioning
confidence: 99%
“…Flora & Goldschmidt 1969;Hussain & Clark 1977 ;Goldschmidt & Bradshaw 1981) or room turbulence (Bradshaw 1977). More recently, attention has turned (Mumford 1982 ;Oler & Goldschmidt 1981 ; Antonia et al 19833) towards identifying the presence and properties of the organized large-structure of the flow, primarily through space-time correlation measurements. On the basis of flow-visualization results and quantitative measurements, Gold-Schmidt, Moallemi & Oler (1983) have suggested that a pattern of spanwise eddies, somewhat reminiscent of a Karman vortex street, accounts for the flapping-like motion of the flow and for the regions of flow reversal which occur in the outer part of the jet.…”
Section: Introductionmentioning
confidence: 99%